Direct conversion of toluene into styrene with high selectivity over a composite catalyst. (1st February 2021) - Yu, Qijun; Li, Jinzhe; Wei, Changcheng; Liu, Zhongmin
Graphical abstract: Highlights: The side chain alkylation of toluene is investigated on composite catalysts. The catalyst Na2 B4 O7 -CsX shows high performance, especially for styrene selectivity. A new mechanism is proposed to explain the promoting effect of boron compounds. The reaction conditions and the catalyst deactivation are also investigated deeply. Abstract: Although side-chain methylation of toluene with methanol to produce styrene has been investigated in the past decades, commercial application of this process is still a great challenge due to the lack of efficient catalysts. Here we present a bifunctional catalyst composed of dehydrated sodium borate (Na2 B4 O7 ) and zeolite (CsX) that yields a high selectivity to styrene (89.6%) with a relative high toluene conversion (9.57%). Na2 B4 O7 not only contributes to the formation of the reaction intermediate formaldehyde but also constructs the frustrated Lewis pairs (FLPs) with basic sites on the zeolites, which could activate C–H bond in the methyl group of toluene more efficiently. Thus, the crucial role of boron species is revisited. The nature of cesium in CsX is found to be important for the reactivity of the bifunctional catalyst. Good reaction performance on composite catalyst Na2 B4 O7 -CsX also depends on the spatial proximity and mass ratio of the two components.